Working Together : Intercultural Academic Leadership : LE11-2082 : Final Report. - Scott, Kim; Bessarab, Dawn; Durey, Angela; Taylor, Kate; Hoffman, Julie; Kickett, Marion; Forrest, Simon; Jones, Sue; Austen, Louise (Office for Learning and Teaching, 2014)
Final report from a project that relates to the Australian Learning and Teaching Council (ALTC) Priority 2: Disciplinary and cross-disciplinary leadership, in this case a model of collaborative, intercultural academic leadership to improve the health outcomes of Indigenous Australians. Focused within the Faculty of Health Sciences the project aimed to improve the learning and teaching outcomes of students (2300 annually) in the core first year unit Indigenous Culture and Health 130 by building the capacity of staff responsible for its coordination and teaching through developing an intercultural academic leadership development program. This project was unique in that it recognised and addressed the ground work and relationship building needed to successfully Indigenise the curriculum. The project strongly aligns with the ALTC objectives by identifying good practice to facilitate national approaches to addressing emerging issues such as recruiting and retaining Indigenous students and staff. The project outcomes have broad applicability by ensuring cross-cultural competency for all students.